1995
DOI: 10.1007/bf00685796
|View full text |Cite
|
Sign up to set email alerts
|

Gender affects doxorubicin pharmacokinetics in patients with normal liver biochemistry

Abstract: We studied the variability in doxorubicin pharmacokinetics in 27 patients, all of whom had normal liver biochemistry tests. Blood samples were collected after the first cycle of single-agent doxorubicin given as an i.v. bolus and plasma levels were measured by high-performance liquid chromatography (HPLC). The relationship of doxorubicin clearance (dose/AUC) with biochemical tests (AST, bilirubin, alkaline phosphatase, albumin, creatinine) and physical characteristics (age, gender, height, weight, tumour type)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 16 publications
1
38
2
Order By: Relevance
“…Both dose and weight influenced V1 when included as single covariates but combining these factors offered no significant advantage. In contrast to the results of Amantea et al (1997) in a larger group of 43 patients who received pegylatedliposomal doxorubicin, body surface area was not found to influence the clearance of PK1, nor was clearance reduced in female patients, as previously shown by Dobbs et al (1995) with standard doxorubicin. However, a larger number of subjects would be required to investigate these influences properly.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Both dose and weight influenced V1 when included as single covariates but combining these factors offered no significant advantage. In contrast to the results of Amantea et al (1997) in a larger group of 43 patients who received pegylatedliposomal doxorubicin, body surface area was not found to influence the clearance of PK1, nor was clearance reduced in female patients, as previously shown by Dobbs et al (1995) with standard doxorubicin. However, a larger number of subjects would be required to investigate these influences properly.…”
Section: Discussioncontrasting
confidence: 86%
“…The elimination half-life of 85 h identified in this analysis was longer than the typical values of 20Ð50 h reported in many studies with doxorubicin (Bronchud et al, 1990;Piscitelli et al, 1993;Dobbs et al, 1995;Jaquet et al, 1996). It is possible that these differences are influenced by sampling strategy.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Interestingly, the AUC for fluorouracil appears higher in females, 24 and doxorubicin, which is a key component of chemotherapy for HL, ES and OS, has demonstrated significant gender-and body compositionrelated differences in pharmacokinetic profile. [30][31][32][33][34] Our studies add to these findings by suggesting that almost all of the survival gap in AYAs may be linked to relative underdosing of males based on current dosing algorithms.…”
Section: Discussionmentioning
confidence: 56%
“…Milano et al (18) reported that the capacity to clear 5-FU is lower in women than in men. Dobbs et al (19) demonstrated that, among patients with normal liver function, men exhibit a higher rate of doxorubicin clearance compared to women. Higher response to chemotherapy in females observed in this study may partly be due to the higher blood concentrations of chemotherapeutic agents.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%